Relationship between physiological quality of soybean seed and field performance - Marcos Filho, Julio (Pesquisa Agropecuaria Brasileira, 2014)
Soybean seeds (Glycine max (L.) Merrill) of Bragg and U.F.V. - 1 cultivars each one collected in different soybean cropping areas were used in a research project designed to study the effect of seed physiological quality on the overall performance of field grown plants, in 1977/1978. The experimental part of this research was conducted at the Seed Technology Laboratory and at the Experimental Field of the Horticultura and Agricultura Department of the Escola Superior de Agricultura 'Luiz de Queiroz", University of São Paulo, Brazil. The seed lots were labelled according to cultivar and place and standardized as to size. Seed quality was evaluated by means of the following tests: standard germination, first-count, rapid aging, radicle and hypocotyl length and speed of seedling emergence; vigor ratings were calculated from the results of the standard germination, first-count and the rapid aging tests. Plant performance was studied in completely randomized field experiments planted in 1977 and 1978; seeds were planted so as to assure stand uniformity among the experimental plots. Approximately twenty days after planting, emergence ( % ), number of plants per meter in the row and plant height were determined, after harvest, the following data were obtained: terminal number of plants, number of racemes per plant and yield. Seedling emergence and plant height was found to be related to differences in physiological quality among seed lots as determined by laboratory tests, whereas there appears to be no yield relation with seed vigor.
Keywords: Glycine max (L.) Merrill; seed; physiological quality; field performance